STUDI KEPUASAN CUSTOMER DI HOTEL CITRADREAM SEMARANG DENGAN PENGARUH TINJAUAN PELANGGAN ONLINE, HARGA DAN KEPUTUSAN CUSTOMER MENGINAP SEBAGAI PREDIKTOR - Rama Yudha Hastungkoro; Andhi Supriyadi (LPSDI Bina Patria, 2022)
This research was conducted at Hotel Citradream Semarang with the aim of analyzing and explaining the impact of online customer reviews, prices and customer stay decisions on customer satisfaction. Information is collected through forms and interviews. Consisting of 94 respondents, the sample used in the research. It is anticipated that this research can provide valuable information for management. The information obtained is processed by carrying out both quantitative statistical analysis and descriptive analysis. Multiple regression analysis is used quantitatively to evaluate the impact of the independent variable influencing the dependent variable, as well as test the model and hypothesis. It is crucial to do a validity and reliability test before to administering this exam. The regression analysis's findings indicate that the rise in customer satisfaction is impacted directly or indirectly by online customer reviews, prices, and customer stay decisions. Thus, online customer reviews, prices, customer decisions must be carefully considered so that hotel management can increase customer satisfaction in the following period.